2012
DOI: 10.1519/jsc.0b013e318237ea4f
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Characteristics of Water Polo Players and Efficacy Indices

Abstract: The aim of this study was to define and examine the relationships between the anthropometrical characteristics, maximum isometric grip strength, and competition throwing velocities and efficacy indices in high-level water polo player. Eleven elite trained male water polo players participated in this study. During preseason training, the following measures were taken: standard anthropometry (height, body mass, arm spam, skinfolds, body girths, and skeletal breadths) and grip strength. During official European C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 21 publications
3
19
1
2
Order By: Relevance
“…Unlike the previous researches where a throwing velocity had a statistically significant correlation with the anthropometric indicators (Bloomfield, Blanksby, Ackland, & Allison, 1990), such a statement is not proven in this study, what, on the other side, entirely correspond to the findings by Ferragut et al (2011b) and Alcaraz et al (2012), who also shown that the anthropometric indicators used in these studies did not accomplish a statistically significant correlation with a throwing velocity. A very interesting data is one offered by Milanović and Vuleta (2013) presenting that a body height, body mass and arm span have no correlations with player's performances in offensive and defensive activities.…”
Section: Figure 11contrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike the previous researches where a throwing velocity had a statistically significant correlation with the anthropometric indicators (Bloomfield, Blanksby, Ackland, & Allison, 1990), such a statement is not proven in this study, what, on the other side, entirely correspond to the findings by Ferragut et al (2011b) and Alcaraz et al (2012), who also shown that the anthropometric indicators used in these studies did not accomplish a statistically significant correlation with a throwing velocity. A very interesting data is one offered by Milanović and Vuleta (2013) presenting that a body height, body mass and arm span have no correlations with player's performances in offensive and defensive activities.…”
Section: Figure 11contrasting
confidence: 99%
“…Although the throwing velocity did not accomplish a statistically significant correlation with any morphological attribute, in this way we can indirectly conclude that a higher throwing velocity was accomplished by elite water polo players who, first of all, hada bigger body mass and higher body heights. After that, it can be said that the findings from this study directly coincide with the statement by Alcaraz et al (2012) who concluded that exist a strong and significant correlation between conditioning and performance factors with anthropometrical parameters in elite water polo players, accordingly, with statement by Alcaraz et al (2011), who argue that a physical (strength, power, throwing velocity) and anthropometrical factors are important for determining the outcomes in water polo.…”
Section: Figure 11supporting
confidence: 87%
“…A similar shot speed between groups was also found by Vila et al (2011), with values in agreement with the data from official games (Canossa et al, 2016), but lower than those from standardised testing conditions (Melchiorri et al, 2015), probably due to game constraints and the players' option to perform a shot action aiming its accuracy (Ferragut et al, 2015). These aspects might explain the slower shot speeds close to the Journal of Human Kinetics -volume 72/2020 http://www.johk.pl goal, higher speeds at distances further from the goal and the consequent differences in shot speed distribution according to the field area (Alcaraz et al, 2012). Despite recognising shooting speed as being vital to the match outcome, since it hampers the actions of the defence and the goalkeeper, accuracy also seems crucial.…”
Section: Discussionmentioning
confidence: 97%
“…Many of the talent agencies are focused on anthropometric variables since the structural characteristics of the individuals cannot be easily modified [15,16]. In some sport fields, given the diversity of the skills in that field, physical characteristics of the players play a significant role in developing the team's technical and tactical training program.…”
Section: Introductionmentioning
confidence: 99%